Improving the context for inclusion [ personalising teacher development through collaborative action research - Howes, Andy; Davies, Susan; Fox, Samantha (Improving learning TLRP, 2009)
This text addresses the requirement for increasing the multi-agency capacity around young people. It analyses accounts of collaborative action research to show how teachers can engage with inclusion for the benefit of themselves and their pupils